2017
DOI: 10.1089/lrb.2016.0031
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Direct Evidence of the Superficial Lymphatic Drainage Effect of Intermittent Pneumatic Compression Treatment for Lower Limb Lymphedema

Abstract: Sequential programs and high pressure resulted in a faster lymphatic flow than other modes. These results suggest that a greater treatment effect could be obtained by adjusting the mode of treatment and the pressure of IPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…In their 2013 study, Zaleska et al [27] reported that a high pressure of about 120 mm Hg and at least 50 seconds of compression are required to produce efficient tissue fluid pressure and generate proximal flow. In a study that examined lymph circulation after varying combinations of IPC interventions, including simultaneous inflation of 6 chambers, sequential inflation of chambers, sequential deflation from the proximal to distal (6–1), and sequential deflation in the order of 6, 4, 2, 5, 3, and 1, along with varying pressures (45 and 90 mm Hg), no differences were shown in lymph circulation according to the method of inflation, deflation, or the level of pressure among healthy people [12] . Participants in our study were healthy adults with leg swelling and pain caused by prolonged standing work; thus, a relatively high pressure of 90 to 130 mm Hg was applied, which led to swelling and pain reduction without any serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their 2013 study, Zaleska et al [27] reported that a high pressure of about 120 mm Hg and at least 50 seconds of compression are required to produce efficient tissue fluid pressure and generate proximal flow. In a study that examined lymph circulation after varying combinations of IPC interventions, including simultaneous inflation of 6 chambers, sequential inflation of chambers, sequential deflation from the proximal to distal (6–1), and sequential deflation in the order of 6, 4, 2, 5, 3, and 1, along with varying pressures (45 and 90 mm Hg), no differences were shown in lymph circulation according to the method of inflation, deflation, or the level of pressure among healthy people [12] . Participants in our study were healthy adults with leg swelling and pain caused by prolonged standing work; thus, a relatively high pressure of 90 to 130 mm Hg was applied, which led to swelling and pain reduction without any serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that examined lymph circulation after varying combinations of IPC interventions, including simultaneous inflation of 6 chambers, sequential inflation of chambers, sequential deflation from the proximal to distal (6–1), and sequential deflation in the order of 6, 4, 2, 5, 3, and 1, along with varying pressures (45 and 90 mm Hg), no differences were shown in lymph circulation according to the method of inflation, deflation, or the level of pressure among healthy people. [ 12 ] Participants in our study were healthy adults with leg swelling and pain caused by prolonged standing work; thus, a relatively high pressure of 90 to 130 mm Hg was applied, which led to swelling and pain reduction without any serious adverse events. Thus, based on our study in combination with previous research, high pressure IPC dosage for about 30 minutes seems to be an appropriate intervention for leg pain and swelling following prolonged standing at work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid lines show the sample median, while dashed lines depict the sample mean. filtration in the calf, even reducing fluid accumulation relative to supine baseline (Kitayama et al, 2017;Tran and Argáez, 2017). This fluid was instead mobilized back into the effective circulating volume, perhaps with some enhancement in lymphatic drainage, improving SV, allowing blood pressure to be maintained at a reduced HR, and thus increasing cardiovascular autonomic reserve, improving CBFv, and delaying presyncope.…”
Section: Discussionmentioning
confidence: 99%
“…Окремі дані дозволяють опосередковано обґрунтувати можливість дезінтоксикаційного ефекту та пояснити ймовірний механізм. Зокрема, відомо, що процедури пневмопресингу можуть вести до окиснення проміжних метаболітів [6]; підвищення проникності біологічних мембран; прискорення руху лімфи [7] і збільшення об'єму лімфатичного відтоку; активації сечоутворення [8]. Ряд досліджень за участю спортсменів показав, що короткотривалі метаболічні зміни незначні і, можливо, залежать від методики пневмопресингу.…”
Section: Orcid Id: 0000-0002-0875-462xunclassified